STUDENTS SATISFACTION IN MAJOR PUBLIC UNIVERSITY: A PRE-PANDEMIC STUDY IN BANGLADESH - Imran, Md. Ali; Ahmed, Ikbal; Bhuiyan, Md. Mazharul Islam; Rahid, Abu Obida; Begum, Noorjahan (American International Journal of Social Science Research, 2021)
Student satisfaction is entitled to the standard facilities enjoyed by the students according to the cherished and standardised criteria. In Bangladesh, public universities are furnishing education to a myriad of students. But in terms of catering privileged prerequisites compare to top-class universities over the globe, we are far behind. To investigate the level of student gratification, we constructed some benchmark questions and collected feedback from five top-rated university students. We focused on various conglomerate issues faced by public university students, aiming to scrutinise the substantive outline. Advance statistical tools are used to analyse the data. We revealed some malaise from the student response. Quite a few strategies and reciprocity from the jurisdiction can quench the environment, which will augment the student satisfaction level.